Using rectangular trace to reduce the crosstalk of the coupled microstrip lines - Hussein, Ahmed Ali (Science Publishing Corporation Inc ijet@sciencepubco.com, 2016)
New electronic products must have high-speed, small size and lower voltages supply. With such layout, signal integrity (SI) becomes an actual important issue because sensitive equipment is affected on electromagnetic interference (EMI). Crosstalk is a major factor in signal integrity (SI) of printed circuit boards (PCBs). Crosstalk noise is usually represented in terms of Near-End crosstalk (NEXT) and Far- End crosstalk (FEXT). Crosstalk is a common problem that degrades circuit performance. To reduce this problem, via hole-fences connected by guard trace between double microstrip lines are used, in this case the crosstalk will be reduce by 6 dB than use 3W rule, but when it replaced by rectangular metal the crosstalk was reduce by 7dB, is better than use via hole-fences by 1 dB. The simulation result was done by using FEKO 5.5 simulator. © 2016, Ahmed Ali Hussein.
Keywords: FEXT; NEXT; SI; Via fences